Financial Mechanism for Managing the Environmental Innovation Development of the Economy in Ukraine - BORISOVA, Victoria; SAMOSHKINA, Iryna; RYBINA, Larysa; SHUMKOVA, Olena (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.v11.7(47).03, 2020)
The article substantiates the directions of improving a financial mechanism for managing the environmental innovation development of the Ukrainian economy. It presents an in-depth analysis of conceptual foundations of the formation of a system of principles, goals and criteria for ensuring the adequacy of a financial management mechanism with a special focus on the features of environmental innovation development. For optimal reallocation of a resource component, the necessity for systematic application of fiscal and credit management tools is justified. To ensure maximum growth of environmental innovation capacity of the economy the authors have improved a mechanism for developing an optimal set of target financing programs, analyzed the financial methods of managing the environmental innovation development of economy. The paper focuses on the nature and content of the concept “financial mechanism for managing the environmental innovation development of economy”, which is proposed to be understood as a system of actions of financial methods and levers on the basis of relevant legal, information and regulatory support aimed at the most efficient development of the environmental innovation capacity of economy through optimal reallocation of the resource component of this potential. This enables, on the basis of a systematic analysis of financial relations that originate from environmental innovation development, to determine the main directions of their transformation under the influence of changes in the financial management mechanism. The subject of the research is the economic relations that arise between state and local government bodies and business entities regarding the allocation and reallocation of financial resources in managing the environmental innovation development of economy. In order to achievie the goal of the article, the authors have used the general scientific and special methods of cognition, fundamental provisions of general economic theory, the theory of economic development, evolutionary economics, economics and finance of nature management.